A Novel Communication Pathway Between Lysosomes and Mitochondria Is Disrupted in Alzheimer's Disease. (July 2019) - Norambuena, Andrés; Bloom, George S.
A growing body of evidence supports the idea that organelles talk to each other. This communication is characterized by either physical interactions, functional associations mediated by signaling molecules, or both. This flow of information allows the orchestration of proper cellular metabolic responses to the ever-changing extracellular environment. Mitochondria, the cell's principle metabolic factories, have emerged as a major player that not only influence the functions of other organelles, such as the endoplasmic reticulum, nuclei, and lysosomes, but as recently shown by our group, mitochondria also receive functionally critical information from lysosomes. This process was found to be mediated by the lysosome-associated mechanistic target of rapamycin complex 1, another major regulator of cellular metabolism. As discussed here, disruption of this lysosome-to-mitochondria signaling pathway may underlie the early pathogenesis of Alzheimer's disease.